ANALYSIS OF IMPLEMENTATION BARRIERS FOR K3 ON WIYUNG SEJAHTERA HOSPITAL CONSTRUCTION PROJECT, SURABAYA - Ismail Halim; I Nyoman Dita Pahang Putra (Jurnal Pensil : Pendidikan Teknik Sipil, 2025)
The implementation of occupational health and safety (OHS) is one of the key factors in a project. This study aims to analyze the factors and constraints in implementing OHS by distributing questionnaires to contractors, consultants, and hospital employees. Based on the data, nine factors were identified: workplace safety on the project (X1), equipment and work clothing (X2), fire safety (X3), protection of the public (X4), worker health (X5), worker communication (X6), general factors (X7), obstacles from the company's side (X8), and obstacles from the workers' side (X9). The results were tested for validity, reliability, classical assumptions, and CFA, and then analyzed descriptively and using Pearson correlation analysis. The Pearson correlation analysis between factors showed that fire safety (X3) and public protection (X4) had the highest correlation, 0.699, indicating a very strong relationship. The relationship between factors and indicators with the highest correlation was between the general factor (X7) and the indicator of thoroughly identifying past workplace accidents (X7.5), with a very strong correlation of 0.881. The highest correlation between indicators was between the indicator of limiting flammable materials (X3.3) and providing storage for flammable materials (X3.4), with a very strong correlation of 0.810.